AN ANALYSIS OF TEACHERS’ PEDAGOGIC COMPETENCE IN TEACHING ENGLISH YOUNG STUDENTS AT SMPN 1 BARAKA - Djihat, Assalam; Ampa, Andi Tenri; Mallapiang, Yassir (FKIP Unismuh Makassar, 2024)
This research is ” An Analysis Of Teachers` Pedagogic Competence In Teaching English Young Students at SMPN 1 Baraka “. The purpose of this study is to examine the pedagogical competence that posses by the teacher in SMPN 1 BARAKA namely managing young students classroom and make the students stay curious and enthusiasm to learn english. This study was conducted to describe how teachers manage young students classroom, find out how well the teachers understand the needs of their young students and to see if the teachers pedagogical competencew have an impact on the students desire to learn english. In this study , researcher used purposive sampling to collect data. in this study, there was 4 class as observation data and 2 teachers as resource persons to interviews. This research was conducted at SMPN 1 BARAKA. The result of this study indicate that Based on the results of the observation and interview, the conclusion of this study are presented based on the data obtained which has been analysed. From all data analysis on how do the teachers able to manage the students and make them stay curious and enthusiasm to learn English. It can be concluded that experience can be one of the factors which affect the understanding and implementation of pedagogical competence specifically the classroom management. In addition, pedagogical competence is the ability of teaching that cannot be comprehended in short time.